Preoperative Fasting Duration as a Potential Predictor of Glycemic Instability in Non-Diabetic Emergency Surgery Patients: A Prospective Observational Pilot Study - Mustaqiem Isda; Aswoco Andyk Asmoro; Ristiawan Muji Laksono; Rudy Vitraludyono (Open Access Indonesian Journal of Medical Reviews, 2025)
Preoperative fasting is a cornerstone of anesthetic safety, yet in emergency surgery, fasting periods are frequently prolonged and unregulated. The metabolic consequences of such extended fasting in non-diabetic patients, who are often assumed to be metabolically resilient, are poorly understood. This pilot study aimed to investigate the association between prolonged fasting and pre-induction glycemic instability. We conducted a prospective, observational pilot study at a tertiary referral hospital, enrolling 30 non-diabetic adult patients (ASA I-E/II-E) undergoing emergency surgery. The primary exposure was preoperative fasting duration, analyzed as both a continuous variable and a dichotomized category (≤8 vs. >8 hours). The primary outcomes were pre-induction blood glucose levels, analyzed continuously and with two categorical thresholds: glycemic instability (<85 mg/dL) and clinically significant hypoglycemia (<70 mg/dL). Associations were assessed using Chi-Square tests and Spearman's rank correlation. A majority of patients (60%) fasted for >8 hours. A strong negative correlation was found between the duration of fasting and pre-induction blood glucose levels (Spearman's ρ = -0.78, p<0.001). Using the <85 mg/dL threshold, 83.3% of patients fasting >8 hours exhibited glycemic instability, compared to 25% of those fasting ≤8 hours (p=0.002). Using the standard <70 mg/dL threshold, 55.6% of patients fasting >8 hours developed clinically significant hypoglycemia, compared to 8.3% of those fasting ≤8 hours (p=0.011). In conclusion, this pilot study provides a strong preliminary signal that prolonged preoperative fasting is significantly associated with a decline in blood glucose and an increased incidence of both glycemic instability and clinically significant hypoglycemia in non-diabetic emergency surgical patients. These findings challenge the assumption of metabolic security in this population and underscore the urgent need for larger, definitive studies. Routine pre-induction glucose monitoring should be strongly considered as a potential safety standard in this vulnerable group.